Behavioral Differences In Seeking Help For Mental Health Among Generation Z From The Kodi People Group And The Madurese Ethnic Group - Yohanis Dodok; Ahmad Guntur; Indriyawati; Kurniawan Erman Wicaksono (Journal of Applied Nursing and Health, 2022)
Background: mental health problems in generation Z of the Kodi People Group and Madurese ethnic group in their behavior in seeking mental health assistance. The purpose of this study is to analyze the differences in the behavior of mental help seeking from Generation Z in the Kodi people group and Madurese ethnic group. Methods: This research used quantitative research method, namely, the survey method. The subjects of this study were Generation Z from the Kodi people group and the Madurese who have experienced mental health problems such as stress, anxiety, depression, suicidal thought, drug use, and physical illness. The sampling technique used was purposive sampling with a total of 200 respondents from Generation Z. This study used the instrument of General Help-Seeking Questionnaire Vignette Version (GHSQ-V). The hypothesis test in this study was a paired t-test. Results: 33% of respondents from the Kodi people group had behavior in seeking mental health assistance that was categorized as "high". Meanwhile, respondents from the Madurese ethnic group also had behavior that was categorized as "high", which was 33.5%. The Results of T-Test Analysis of Behavior in seeking mental health assistance among Generation Z from the Kodi people group and the Madurese ethnic group was 0.905 Conclusion: it can be said that there is no significant difference in the behavior of seeking mental health help between Generation Z of the Kodi people group and the Madurese ethnic group. The recommendation of this research is as a preliminary study in culturally sensitive based mental health nursing. so that future research can use culturally sensitive-based mental health nursing interventions